Differential scanning calorimetry research of biodegradable films for confectionery and bakery products - Shulga, Oksana; Chorna, Anastasia; Kobylinskyi, Sergiy (My University, 2017)
Biodegradable films for bakery and confectionery products using differential scanning calorimetry are studied in this work. Expediency for the use of biodegradable films for marmalade, gingerbread, bakery products, and fondant confectionery according to organoleptic characteristics is established. The influence of the type of starch on film structure is studied with DSC analysis. DSC analysis was used to determine functionality of using glycerol as plasticizer, as this can reduce the temperature of melting point and glass transition of original compounds.
Keywords: biodegradable films; edible film; differential scanning calorimetry; confectionary; bakery products; биоразлагаемые пленки; сьедобные пленки; диференциально сканирующая колориметрия; кондитерские изделия; хлебобулочные изделия; біодеградабельні плівки; їстівні плівки; диференційно скануюча колориметрія; кондитерські вироби; хлібобулочні вироби; кафедра експертизи харчових продуктів